1995
DOI: 10.1007/bf00032673
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the yeast FLP recombinase in Arabidopsis

Abstract: The coding sequence for FLP recombinase, originally from the 2 mu plasmid of Saccharomyces cerevisiae, was introduced into Arabidopsis behind the cauliflower mosaic virus 35S promoter. FLP activity was monitored by the glucuronidase activity resulting from inversion of an antisense-oriented GUS reporter gene flanked by a pair of FRT target sites in inverted repeat. FLP-dependent Gus activity was observed in both transient assays and transgenic plants. The FLP system will be useful for a variety of in planta ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 30 publications
(36 reference statements)
0
22
0
Order By: Relevance
“…Transgene excision-activation via site-specific recombination in extra-and intra-chromosomal environments has been so far demonstrated in a growing number of plant species including tobacco Ow 1990, 1991;Odell et al 1990;Onouchi et al 1991;Bayley et al 1992;Russell et al 1992;Lloyd and Davis 1994;Kilby et al 1995: Bar et al 1996Gidoni et al 2001b), Arabidopsis (Russell et al 1992;Kilby et al 1995;Onouchi et al 1995;Sonti et al 1995;Luo et al 2000;Hoff et al 2001;Marjanac et al 2008), petunia (Que et al 1998;Coppoolse et al 2003), tomato (Stuurman et al 1996;Coppoolse et al 2003;Zhang et al 2006, Gidoni et al unpublished results), potato (Cuellar et al 2006;Kondrak et al 2006), soybean (Li et al 2007), strawberry (Schaart et al 2004), wheat (Srivastava et al 1999), rice (Endo et al 2002;Hoa et al 2002;Toriyama et al 2003;Radhakrishnan and Srivastava 2005;Sreekala et al 2005;Hu et al 2008), maize (Lyznik et al 1996;Srivastava and Ow 2001;Zhang et al 2003;Kerbach et al 2005), turfgrass (Hu et al 2006), Brassica juncea (Indian mustard; Arumugam et al 2007), citrus (Ballester et al 2007), aspen, and snapdragon . This progress, along with progress made in development of tran...…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 98%
See 1 more Smart Citation
“…Transgene excision-activation via site-specific recombination in extra-and intra-chromosomal environments has been so far demonstrated in a growing number of plant species including tobacco Ow 1990, 1991;Odell et al 1990;Onouchi et al 1991;Bayley et al 1992;Russell et al 1992;Lloyd and Davis 1994;Kilby et al 1995: Bar et al 1996Gidoni et al 2001b), Arabidopsis (Russell et al 1992;Kilby et al 1995;Onouchi et al 1995;Sonti et al 1995;Luo et al 2000;Hoff et al 2001;Marjanac et al 2008), petunia (Que et al 1998;Coppoolse et al 2003), tomato (Stuurman et al 1996;Coppoolse et al 2003;Zhang et al 2006, Gidoni et al unpublished results), potato (Cuellar et al 2006;Kondrak et al 2006), soybean (Li et al 2007), strawberry (Schaart et al 2004), wheat (Srivastava et al 1999), rice (Endo et al 2002;Hoa et al 2002;Toriyama et al 2003;Radhakrishnan and Srivastava 2005;Sreekala et al 2005;Hu et al 2008), maize (Lyznik et al 1996;Srivastava and Ow 2001;Zhang et al 2003;Kerbach et al 2005), turfgrass (Hu et al 2006), Brassica juncea (Indian mustard; Arumugam et al 2007), citrus (Ballester et al 2007), aspen, and snapdragon . This progress, along with progress made in development of tran...…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 98%
“…However, retransformation is lengthy and cross-fertilization-dependent strategies are applicable only for sexually propagated species with relatively short reproduction cycles. Additionally, constitutive overexpression of recombinase proteins may cause aberrant developmental phenotypes in plants (Sonti et al 1995;Que et al 1998;Coppoolse et al 2003). Therefore, alternative approaches based on transient gene expression have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Some site-specific recombination systems have been shown to function efficiently in heterologous cellular environments. For example, FLP/FRT from the 2 lm plasmid of Saccharomyces cerevisiae (Broach et al 1982), or Cre/lox from E. coli phage P1 (Austin et al 1981) have been shown to catalyze DNA recombination in tobacco (Lioyd and Davis 1994;Qin et al 1994;Bar et al 1996;Bayler and Hess 2005), Arabidopsis (Odell et al 1990;Dale and Ow 1991;Bayler et al 1992;Russell et al 1992;Kilby et al 1995;Osborne et al 1995;Sonti et al 1995;Luo et al 2000), tomato (Stuurman et al 1996), maize and rice (Lyznik et al 1993(Lyznik et al , 1995Hoa et al 2002;Radhakrishnan and Srivastava 2005;Sreekala et al 2005) as well as wheat (Srivastava et al 1999). This provides an excellent tool for controlled modification of plant genomes including chromosomal deletions, inversions, transpositions (Ow 1996;Luo and Kausch 2002) or site-specific gene targeting (Albert et al 1995;Srivastava and Ow 2002).…”
Section: Introductionmentioning
confidence: 95%
“…Wu et al, 2000;Johansson et al, 2003;Hao et al 2005;Filichkin et al, 2006b). Although gene excision has been used in poplar, most notably as part of the MAT system (Ebinuma et al, 1997;Matsunaga et al 2002;Zelasco et al, 2007), a number of other useful and well studied excision systems such as CRE/LOX (Marjanac et al, 2008) and FLP/FRT (Sonti et al, 1995) have not, to our knowledge, ever been characterized for their effectiveness in poplar. Nevertheless, technological advance in other species seem to be transferable to poplar (Fig.…”
Section: Future Prospects and Challengesmentioning
confidence: 99%